Myelodysplastic Syndrome Overview in the Elderly: Case Report - Harmita, Devi; Wulida Litaqia; Ainun Najib Febrya Rahman; Hanafi; Haryati Septiani; Dikki Saputra (Journal of Community Development and Disaster Management, 2025)
Background: Myelodysplastic syndrome (MDS) is a hematopoietic disorder characterized by cytopenia, dysplasia, and genetic abnormalities that can transform into acute myeloid leukemia. MDS cases generally occur in children and adults. This case report involves a 75-year-old elderly individual with no history of MDS or family illness. Purpose of the Study: This study serves as a reference for screening the nursing perspective of MDS in the elderly. Methods: This research is a descriptive case report of 1 case. Results: A 75-year-old elderly patient with 1 month of weakness and pallor, blood pressure of 140/90 mmHg with controlled hypertension for 1 year. Laboratory results showed correlation with MDS symptoms: leukopenia (leukocytes 2.85 x 10^3/µl), thrombocytopenia (platelets 1,000/µl), and anemia (Hb 4.3g/dl). Conclusions: Hematological data support the patient experiencing MDS. Additionally, the patient's exposure to pesticides for 40 years also strongly supports the occurrence of MDS as it is a triggering factor for MDS.